Incentivierung des Managements bei Unternehmenskäufen/Buy-Outs mit Private Equity Investoren - eine empirische Untersuchung - Christoph Schalast; Marius Buxkaemper; Christian Büchler; Gregor Wedel (Frankfurt School of Finance & Management, 2011)
Since years, incentives for the management have become a standard upon acquisitions of companies by Private Equity Investors - so-called Buy-Outs. However, until this date there are no empirical studies available on the arrangements of management participations and potential conflicts of interest especially on occasion of sales from one Private Equity Investor to another - so-called Secondary Buy-Outs. This present study is based on a survey among Private Equity Investors and Management Teams in companies controlled by Private Equity Investors. It shows a high degree of sensibility of all parties concerned for the issue of incentives and the potential conflict of interest involved with it. It also showed that market standards for management incentives have developed in the meantime. In practice, the instrument to prevent conflicts is therefore the transparency of the transaction. The only way to prevent criminal and civil consequences (damages) for the managers involved, as well as obstructing or even frustrating the process as a whole, is an open and transparent communication about the selling process and possible concepts of incentives between all parties concerned, i.e. seller, buyer and the management involved. Despite the frequency of such transactions there are - until today - no market standards or guide lines for this necessary transparency. The present study intends to create initial groundwork for this.
Keywords: K12; K19; K22; K29; 330; Management Buy-Out; MBO; Management Buy-In; MBI; Leveraged Buy-Out; Private Equity; Secondary Buy-Out; Managementbeteiligung; Beteiligungsvertrag; Bad-Leaver/Good-Leaver; Interessenkonflikt; Beteiligungsquote; Garantien; Exit; Incentivierung; Reporting; Transparenz